PENGARUH HUMAN RELATION (HUB. ANTAR MANUSIA) DAN BUDAYA ORGANISASI TERHADAP ETOS KERJA KARYAWAN PADA PT. ANGKASA PURA II (PERSERO) KANTOR CABANG BANDAR UDARA SULTAN SYARIF KASIM II PEKANBARU - Sihite, Tommy Paniel; Marnis, Marnis; Nuryanti, Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Angkasa Pura II (Persero) Branch Airport Sultan Syarif Kasim Ii Pekanbaru. in order to determine the effect of human relations (human relations) and organizational culture simultaneously to the work ethic of employees at PT. Angkasa Pura II (Persero) Branch Airport Sultan Syarif Kasim II Pekanbaru. This study uses primary data obtained from interviews and giving questionnaires to all employees at PT. Angkasa Pura II (Persero) Branch Airport Sultan Syarif Kasim II Pekanbaru. Secondary data were obtained relating to the object and the organizational structure of the population in this study were all employees numbering 70 people and sampled. The analytical method used in this study is the linear regression method berganda.Dari results of testing that was done, simultaneous regression test (Test-F) indicates that the variable human relations (human relations) and organizational culture simultaneously significant effect on the employee's fix ethos. From the results of the partial test (t-test) showed that the variables of human relations (human relations) and organizational culture significantly influence employee Work Ethics. The result of the calculation of the coefficient of determination (R2) is approximately 6.08%, which means, variable human relations (human relations) and organizational culture together affect the Work Ethic, while the rest influenced by other variables not examined in this study.Keywords: Human Relations, Organizational Culture and Work Ethics Employees